High skills/giftedness in brazilian research: a study on the productions in postgraduate programs in Brazil in the period of 2002-2020 (Research, Society and Development, 2021)
According to the National Policy on Special Education from the Perspective of Inclusive Education, published in 2008, the special student body consists of students with disabilities, global developmental disorders, and high skills/giftedness. Although there are several difficulties in treating the three groups, they are even greater in the area of ​​high skills/giftedness due to the scarcity and lack of dissemination of materials on the subject. In this sense, the research seeks to verify how it has been researched in Brazil. To this end, we conducted a survey of the works produced by graduate programs between 2002 and 2020 and cataloged in the database of the Brazilian Digital Library of Theses and Dissertations, linked to the Brazilian Institute of Information in Science and Technology, of the Ministry of Science, Technology, and Innovation. It is a state-of-the-art research, of bibliographic and documentary nature, and it has a descriptive character. After reading and analyzing the abstracts, 108 surveys were selected, of which 24 were theses and 84 dissertations, with 2018 standing out as the year with the highest production (19%). As for geographic location, there is a predominance of the Southeast (46%), followed by the South (34%), North (9%), Midwest (8%), and Northeast (3%). The most discussed topics were assessment, assistance strategies, teacher training, family expectations, creativity, and multiple intelligences. Theoretical studies indicate the need and the results achieved confirm the importance of continuing studies on the subject investigated, especially concerning educational policies and their effectiveness in the school context.